A stochastic methodology for predictions of the environment created by multiple microvibration sources. (26th May 2015) - Remedia, M.; Aglietti, G.S.; Richardson, G.
Abstract: It is well documented that at frequencies beyond the first few modes of a system, the Finite Element Method is unsuitable to obtain efficient predictions. In this article, it is proposed to merge the efficiency of the Craig–Bampton reduction technique with the simplicity and reliability of Monte Carlo Simulations to produce an overall analysis methodology to evaluate the dynamic response of large structural assemblies in the mid-frequency range. The method (Craig–Bampton Stochastic Method) will be described in this article with a benchmark example shown and implemented in the theory of the dynamic coupling extended to the case when multiple sources of microvibrations act simultaneously on the same structure. The methodology will then be applied to a real practical application involving the modern satellite SSTL 300 S1.